Changes in the T-lymphocyte subpopulation (CD+/CD8+) in the blood of patients following kidney transplant and during the acute rejection episode - Hökl, J; Filkulka, J; Sobotová, D; Cerný, J (Czechoslovak medicine, 1991)
A study was made of changes in the ratio of CD4+/CD8+ in patients who had received cadaverous kidneys and who were under treatment with a combination of cyclosporin A + azathioprine + cor ticosteroids. The results showed that one month after the transparent there was a significant drop (P less than 0.05) in the immunoregulation index compared with the pretransplantation values. Throughout the whole period a correlation (r = -0.65, P less than 0.05) was found between the CD4+/CD8+ ratio and serum, creatinine. In recipients with acute rejection episode no significant difference was found between the CD4+/CD8+ values before the rejection episode (7 +/- 1 days and 3 +/- 1 days) and after it was diagnosed. The introduction of monoclonal antibodies specific for determinants in T-lymphocyte transplantation. Many authors have investigated changes in the CD4+ (helper inducer) to subpopulations (1) made possible immunological monitoring following the organ CDB+ (cytotoxic suppressor) ratio following the organ transplant (2, 3, 4, 5). Some reports (6, 7) have indicated that during rejection of a transplanted kidney there is a rise in the immunoregulation index (CD4+/CD8+), while other works (8, 9) failed to confirm this. Our work presents the dynamics of changes in the CD4+/CD8+ ratio in peripheral blood of recipients of cadaverous kidney transplants, and points to changes in the immunoregulation index before and during acute rejection episodes.
Keywords: CD4 Antigens; antigeny CD4; Humans; lidé středního věku; kreatinin; Graft Rejection; Female; dospělí; lidé; Creatinine; T-lymfocyty - podskupiny; cyklosporiny; T-Lymphocyte Subsets; Adult; transplantace ledvin; ženské pohlaví; Male; Middle Aged; antigeny CD8; diferenciační antigeny T-lymfocytů; Antigens, Differentiation, T-Lymphocyte; Kidney Transplantation; mužské pohlaví; Acute Disease; CD8 Antigens; akutní nemoc; rejekce štěpu; Cyclosporins